2016
DOI: 10.4081/jlimnol.2016.1313
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the marbled crayfish in Slovakia: beginning of an invasion in the Danube catchment?

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 43 publications
0
32
0
1
Order By: Relevance
“…Our results also provide detailed genetic information about the marbled crayfish population on Madagascar. While increasing numbers of marbled crayfish introductions have been reported in northern countries [11][12][13][14][15][16] , there are currently no scientific records of active range expansions. This contrasts with the situation on Madagascar, where rapid invasive spread is not only facilitated by anthropogenic distribution, but also supported by favourable environmental conditions, such as relatively high temperatures and a dense network of freshwater habitats 41,42 ( Supplementary Fig.…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also provide detailed genetic information about the marbled crayfish population on Madagascar. While increasing numbers of marbled crayfish introductions have been reported in northern countries [11][12][13][14][15][16] , there are currently no scientific records of active range expansions. This contrasts with the situation on Madagascar, where rapid invasive spread is not only facilitated by anthropogenic distribution, but also supported by favourable environmental conditions, such as relatively high temperatures and a dense network of freshwater habitats 41,42 ( Supplementary Fig.…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%
“…8 ). Subsequent distribution via the pet trade and anthropogenic releases resulted in increasing numbers of wild populations in several countries [9][10][11][12][13][14][15][16] . The propagation of marbled crayfish is facilitated by their parthenogenetic mode of reproduction and their high fecundity 17 , which allows the establishment of large populations from single animals 18 , and may serve as a model for the spread of invasive species.…”
mentioning
confidence: 99%
“…Less information on negative effects is known from European localities inhabited by the marbled crayfish (Lipták et al, 2016) because its viable populations were found only recently. For example, populations in Germany and Slovakia were found in 2010 (Jansky and Mutkovič, 2010;Chucholl et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Its origin has been exclusively from aquariumbred individuals inasmuch as native populations of this species are not yet known . Marbled crayfish has become established particularly in Germany (Chucholl et al, 2012), but the species also is reported from Croatia (Samardžić et al, 2014), Italy (Nonnis Marzano et al, 2009;Vojkovská et al, 2014), Hungary (Weiperth et al, 2015;Lőkkös et al, 2016), the Netherlands (Koese, 2008), Slovakia (Jansky and Mutkovič, 2010;Lipták et al, 2016), and Sweden (Bohman et al, 2013). Species availability in the pet market, environmental requirements, and socio-economic predictors such as gross domestic product and human population density have been recognized as key drivers behind the occurrence of marbled crayfish (Perdikaris et al, 2012;Chucholl, 2014Chucholl, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Crayfish got in Europe as an aquarium species and most likely have been infused in Germany reservoirs [5; 6]. As an invasive species marbled crayfish hit the waters of the Netherlands, Italy, Slovakia, Sweden, Croatia and Ukraine [7][8][9][10][11][12][13][14]. The main feature of the marbled crayfish is that its population consists entirely of triploid females and reproduction occurs by parthenogenesis [15].…”
Section: Introductionmentioning
confidence: 99%